Factors Influencing Worker's Intention to Re-accept Seasonal Employment - Matea Matić Šošić; Marija Bečić; Dasen Jasprica (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
The aim of this paper is to explore the factors that influence seasonal workers' intentions to re-accept seasonal employment in the following year in Dubrovnik-Neretva County, Croatia. The analysis is based on dataset drawn from the Seasonal Employment Survey undertaken annually by Dubrovnik regional office of Croatian Employment Service for the period 2013-2015. Binarity of the dependent variable and longitudinal character of the dataset imposed probit regression as a research method. Personal characteristics that turned out to be important in making the mentioned decision were age, educational level, experience, part of the County in which individuals work. Furthermore, wage level, theoretical and practical requirements of the job, as well as teamwork are workplace characteristics that influence worker's intentions of re-accepting the job in the following year. As a final point, satisfaction with the supervisor and workplace satisfaction are statistically significant factors that positively affect intentions to take the same seasonal job next year.
Keywords: 650; Employee loyalty; Seasonal employment; Turnover